Growth Behaviour And Indole Acetic Acid (Iaa) Production By A Rhizobium Sp. Isolated From Cajanus Cajan Plant - R.C SHENDE,; M.B PATIL, (International Journal of Pharma and Bio Sciences, 2011)
The Root nodules of Cajanus Cajan plant produced high amount of (35.56 ug/gm) of Indole acetic acid from Hg plants as compared to the N plant. The IAA was measured maximum from Rhizobium spp. of C.cajan plant at 24h, when the bacteria reached the stationary phase of growth. Mannitol & KNO3 preferred to be a good carbon and nitrogen source for IAA production in all N, Ng, H & Hg Rhizobium strains. The possible relationship between the rhizobial IAA production & legume rhizobia symbioses in relation to stress is discussed.